EVALUATION OF LOW LEVEL LASER THERAPY IN THE MANAGEMENT OF CHEMOTHERAPY-INDUCED ORAL MUCOSITIS IN PEDIATRIC AND YOUNG CANCER PATIENTS: A RANDOMIZED CLINICAL TRIAL - Khadija M Ahmed; Shokhan A. Hussein; Arass J. Noori; Suha N. Abdulateef; Basil K. Abdulla (European Scientific Journal, ESJ, 2015)
Backgrounds: Oral mucositis is a frequent adverse side effect of cancer chemotherapy which is associated with intense oral pain. However, it impairs the quality of life of these patients. Low Level Laser Therapy (LLLT) has been increasingly used in recent years, mostly to accelerate wound healing and to reduce pain. In cancer patients, LLLT has been shown to reduce the incidence and severity of oral mucositis. Objectives: The aim of this study is to evaluate the effect of low level laser therapy in the management of chemotherapy induced oral mucositis. Patients and Methods: The study design used was a randomized clinical trial. A total of 67 cancer patients were eligible to participate in the study. Thus, they were divided randomly into two groups: group 1 irradiated with prophylactic or active laser therapy (AlGalnAs laser diode device with a wave length of 940±15nm, 0.3mW, and a probe emitting dose of 4.2 J/cm²) and group 2 received inactive or sham laser therapy (power output equal to zero). However, for the ethical purpose, once the patients developed ulcerative mucositis, they are irradiated with active laser therapy. The oral assessment was performed daily starting from the first day of the chemotherapy by applying WHO grading system. After 24 hours, the assessment of associated oral pain was carried out every two days with visual analog scale before laser application. Consequently, the associations between variables were analyzed statistically using SPSS version 20. Results: All the patients were presented with some grade of oral mucositis. In the active or prophylactic laser group, the severity of oral mucositis was lower than the inactive or therapeutic laser group. Moreover, the incidence of grade 3 and grade 4 were less observed in the active or prophylactic laser groups than the sham or therapeutic laser groups. In addition, the mean time of healing was significantly lower in the prophylactic laser group than in the therapeutic laser groups (2.05 + 1.89 versus 4.5 + 2.4 days, p> 0,004). Prophylactic laser application was associated with significant reduction of oral pain in comparison with inactive or therapeutic laser therapy (1.18 + 1.09 versus 2.12 + 1.60, p> 0.01). Conclusions: Prophylactic laser therapy is effective in reducing the incidence of sever oral mucositis and in alleviating associated oral pain.